A Study on Knowledge and Attitudes on Emergency Contraceptive Pill among the Females at Selected Educational Institutes of Kamrup District - Phukan Baruah, Aparajita (International Journal of Nursing Research, 2023)
Background: The modernization and technological improvement changing influence younger generation, are more vulnerable to get involved in it, and may involve in premarital sex. Pre-marital sex may lead to an unwanted pregnancy. Most of these unplanned pregnancies are not carried to full term but aborted often in unhygienic conditions leading to serious consequences. Emergency contraception gives a woman the last opportunity to prevent herself from unsafe abortion. However, one should be aware that emergency contraceptive pills (ECPs) are not recommended for regular use. Materials and Methods: This was a descriptive quantitative study carried out at selected educational institutes, i.e.,in higher secondary schools, junior colleges, and colleges of Kamrup district among 1127 higher secondary and degree female students selected with the help of non-probability sampling technique. Structured knowledge questionnaire with 20 questions on five subheadings and three-point Likert scale with ten positive statements were used to assess the knowledge and attitudes on the ECP. Both the descriptive and inferential statistics were used to analyze the collected data. Result: Of total 1127 females, most of the females, i.e., 763 (67.70%) had moderately adequate knowledge with the aggregate mean knowledge 10.08 and SD 2.933 on ECP, and most of the females, i.e., 844 (74.89%) had an unfavorable attitude toward ECP. Conclusion: Female students do not have adequate knowledge of the ECP and do not have favorable attitudes toward the ECP.